CO-COMBUSTION SLUDGE IPAL PLTU TANJUNG JATI B UNIT 1&2 DENGAN BATUBARA : TINJAUAN ENERGI TERMAL PEMBAKARAN DAN PENGARUH TERHADAP EMISI SOX DAN SLAGGING PADA BOILER - SAC, Ragil Darmawan; Aryanti, Nita; Soetrisnanto, Danny (METANA, 2013)
Abstract Electricity production process at TanjungJati B unit 1&2 Power Plant is also producing B3 waste (sludge) obtained from waste water treatment plant. E-Green principles can encourage company to reduce amount of waste generated. A co-combustion process (re-combusting the sludge with coal in boiler) can be applied to reduce the sludge waste. Previous study literature shows there is no experiment related co-combustion between sludge and coal. Moreover, characteristic of sludge (proximate, ultimate, chemical composition and temperature of ash fusion) effective for combustion and the process are unknown. The aims of this research are to find sludge characteristic, to evaluate caloric value from sludge combustion, to study the effect of co-combustion coal-sludge to emission and potential of slagging formation. The research carried out by proximate analysis (moisture, ash, volatile matter, sulfur and caloric content), ultimate analysis (C, H, S, N, and O), chemical composition of ash (SiO2, Al2O3, Fe2O3, CaO, MgO, K2O, Na2O, TiO2, and PÂ2O5), and ash fusion temperature. Results showedthat thecaloricvalue, sulfurandCaO content are differentsludgewithcoal. The caloric value of sludge is 428.22kcal/kg, sulfur content is 12.46% and CaO content is 34.11%. Caloric value of coal is 6125 kcal/kg, sulfur content is 1.14% and CaO content is 1.73%. The sulfur contentrepresentthe amount of produced SOxemissionsdue to there is no sulfur content at formed ash. The combustion with coal produced 427.318 mg/Nm3 SOx emission. The mixingratiothatstillmeets the standardis(15:1) with711.547mg/Nm3 of SOx emission. Mixing ratio variation show that higher ratio gives higher caloric value, lower sulfur content and decrease slagging index. Based on existing boiler requirement conditions, the mixing ratio of (20:1) and (15:1) is applicable due to have enough caloric value, low slagging index, and not exceed the limit for emission.The optimum condition for co-combustion in this research is ratio (15:1). Higher ratio is recommended for application of co-combustion due to result higher caloric value, lower emission and lower slagging index. Â 38Keywords :Co-combustion, Batubara, Sludge IPAL, Slagging